Robustness of potential biological removal to monitoring, environmental, and management uncertainties. (10th September 2020) - Punt, André E; Siple, Margaret; Francis, Tessa B; Hammond, Phillip S; Heinemann, Dennis; Long, Kristy J; Moore, Jeffrey E; Sepúlveda, Maritza; Reeves, Randall R; Sigurðsson, Guðjón Már; Vikingsson, Gísli; Wade, Paul R; et al.
Abstract: The potential biological removal (PBR) formula used to determine a reference point for human-caused mortality of marine mammals in the United States has been shown to be robust to several sources of uncertainty. This study investigates the consequences of the quality of monitoring on PBR performance. It also explores stochastic and demographic uncertainty, catastrophic events, sublethal effects of interactions with fishing gear, and the situation of a marine mammal population subject to bycatch in two fisheries, only one of which is managed. Results are presented for two pinniped and two cetacean life histories. Bias in abundance estimates and whether there is a linear relationship between abundance estimates and true abundance most influence conservation performance. Catastrophic events and trends in natural mortality have larger effects than environmental stochasticity. Managing only one of two fisheries with significant bycatch leads, as expected, to a lower probability of achieving conservation management goals, and better outcomes would be achieved if bycatch in all fisheries were managed. The results are qualitatively the same for the four life histories, but estimates of the probability of population recovery differ.